YAP mechanotransduction under cyclic mechanical stretch loading for mesenchymal stem cell osteogenesis is regulated by ROCK - Kim, Eunju; Riehl, Brandon D.; Bouzid, Tasneem; Yang, Ruiguo; Duan, Bin; Donahue, Henry J.; Lim, Jung Yul (Frontiers in Bioengineering and Biotechnology, 2024)
While yes-associated protein (YAP) is now recognized as a potent mechanosensitive transcriptional regulator to affect cell growth and differentiation including the osteogenic transcription of mesenchymal stem cells (MSCs), most studies have reported the YAP mechanosensing of static mechanophysical cues such as substrate stiffness. We tested MSC response to dynamic loading, i.e., cyclic mechanical stretching, and assessed YAP mechanosensing and resultant MSC osteogenesis. We showed that cyclic stretching at 10% strain and 1 Hz frequency triggered YAP nuclear import in MSCs. YAP phosphorylation at S127 and S397, which is required for YAP cytoplasmic retention, was suppressed by cyclic stretch. We also observed that anti-YAP-regulatory Hippo pathway, LATS phosphorylation, was significantly decreased by stretch. We confirmed the stretch induction of MSC osteogenic transcription and differentiation, and this was impaired under YAP siRNA suggesting a key role of YAP dynamic mechanosensing in MSC osteogenesis. As an underlying mechanism, we showed that the YAP nuclear transport by cyclic stretch was abrogated by ROCK inhibitor, Y27632. ROCK inhibitor also impaired the stretch induction of F-actin formation and MSC osteogenesis, thus implicating the role of the ROCK-F-actin cascade in stretch-YAP dynamic mechanosensing-MSC osteogenesis. Our results provide insight into bone tissue engineering and skeletal regenerative capacity of MSCs especially as regards the role of dynamic mechanical loading control of YAPmediated MSC osteogenic transcription.